What motivates bridge building across pernicious group divides? The effects of regulatory motives, framing, and fit on increasing constructive engagement across political and racial divisions - Coleman, Peter T.; Phan, Lan H. (Frontiers in Social Psychology, 2024)
Introduction Today, the U.S. and countless other democracies have found themselves dangerously divided across political and racial-ethnic differences. Under these conditions, more extreme actors often wield disproportionate influence, with moderate citizens tending to disengage politically, sparking a vicious cycle. Methods Six studies (N = 2,179) were conducted to investigate ways to mobilize citizens to engage in bridge-building activities fostering intergroup tolerance and compassion. Derived from basic regulatory theories of motivation, we tested the effects of stronger prevention (mitigating negative outcomes) vs. promotion (seeking ideal outcomes) and assessment (evaluating the best way to proceed) vs. locomotion (just “getting it done”) motivational orientations and the fit vs. non-fit framing effects of how the activities were presented on differences in engagement with political and racial bridge-building activities across political, racial, and gender groups in the U.S. We hypothesized that individuals with stronger levels of each of the four motivational mindsets would be more likely to express willingness to engage in bridging activities when they were framed in ways consistent (fitting) vs. inconsistent (non-fitting) with their more chronic orientations. Results and discussion Findings supported our hypotheses with some qualifiers and revealed important political, racial, and gender group differences on motivation and bridge-building for different types of engagement activities.